Optimizing lunar regolith beneficiation for ilmenite enrichment - Kulkarni, Kunal; Fabien Franke, Michel; Jundullah Hanafi, Muchammad Izzuddin; Gesing, Thorsten M.; Zabel, Paul (Frontiers in Space Technologies, 2024)
Over the past few years, the international space industry has focused extensively on advancing technologies to enable prolonged human space exploration missions. The primary limiting factor for these endeavors is the spacecraft's capacity to transport and store essential supplies from Earth to support human life and mission equipment throughout the mission's duration. A sustainable solution for this problem is the utilization of resources found on planetary objects for the operation of the mission which is referred to as In-situ resource utilization (ISRU). Previous lunar missions have identified the presence of oxygen within the lunar regolith, which is necessary for sustaining human life and for producing rocket fuel to support further exploration activities. Oxygen is present in many different minerals within the lunar regolith out of which, ilmenite provides the highest yield of oxygen per unit mass using hydrogen reduction. However, the distribution of ilmenite is neither high nor uniform throughout the lunar surface and therefore, needs additional processing to enable efficient production of oxygen. The additional step is beneficiation, which is an important intermediate step for ilmenite-based oxygen production. The regolith beneficiation testbed discussed in this work is a TRL 4 level representation of the technology and comprises three beneficiation techniques, viz. gravitational, magnetic and electrostatic beneficiation that work sequentially to produce an ilmenite enriched feedstock. This paper discusses the experiments performed to analyze the influence of the process parameters on the beneficiation performance of the testbed. The Formatted: Superscript 2 This is a provisional file, not the final typeset article optimized parameter configuration achieved up to three-fold increase in the ilmenite grade relative to the input with about 32 wt-% of the total ilmenite being recovered in the enriched output. The work has thus produced evidence of the effectiveness of the beneficiation testbed in producing an enriched feedstock while outlining avenues for future improvements.